2013
DOI: 10.1007/s10903-013-9820-x
|View full text |Cite
|
Sign up to set email alerts
|

Changing Blood Lead Levels and Oxidative Stress with Duration of Residence Among Taiwan Immigrants

Abstract: Immigrants lack appropriate health care access and other resources needed to reduce their exposure to preventable environmental health risks. Little is known about the impact of lead exposure and oxidative stress among immigrants. Thus, this study was to examine the differences between the blood lead levels (BLLs) and oxidative stress levels of immigrants and non-immigrants, and to investigate the determinants of increased BLLs or oxidative stress levels among immigrants. We collected demographic data of 239 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Two studies verifi ed elevated SOD activity in the study groups when compared with the controls (Ahamed et al 2008 ;Wieloch et al 2012 ), and 4 studies found no significant changes in SOD activity with raised BLLs (Jin et al 2006 ;Diouf et al 2006 ;Martinez et al 2013 ;Wu et al 2013 ). CAT activity was also signifi cantly higher in participants with higher BLLs in 3 studies (Ahamed et al 2006(Ahamed et al , 2008(Ahamed et al , 2011 but was substantially lower in subjects with higher BLLs in 1 study (Wieloch et al 2012 ).…”
Section: Tablementioning
confidence: 92%
See 2 more Smart Citations
“…Two studies verifi ed elevated SOD activity in the study groups when compared with the controls (Ahamed et al 2008 ;Wieloch et al 2012 ), and 4 studies found no significant changes in SOD activity with raised BLLs (Jin et al 2006 ;Diouf et al 2006 ;Martinez et al 2013 ;Wu et al 2013 ). CAT activity was also signifi cantly higher in participants with higher BLLs in 3 studies (Ahamed et al 2006(Ahamed et al , 2008(Ahamed et al , 2011 but was substantially lower in subjects with higher BLLs in 1 study (Wieloch et al 2012 ).…”
Section: Tablementioning
confidence: 92%
“…Almeida Lopes et al case groups in which participants had not been diagnosed with a disease (2.36 ± 2.7 μg/dL; Table 3 ) (Wieloch et al 2012 ). The most frequently used biomarkers for Pb-induced OS were as follows: GSH (Siddiqui et al 2002 ;Ahamed et al 2006Ahamed et al , 2008Ahamed et al , 2011Diouf et al 2006 ;Jin et al 2006 ;Cabral et al 2012 ), MDA (Siddiqui et al 2002 ;Ahamed et al 2006Ahamed et al , 2008Ahamed et al , 2011Jin et al 2006 ;Cabral et al 2012 ;Wu et al 2013 ), SOD (Jin et al 2006 ;Diouf et al 2006 ;Ahamed et al 2008 ;Martinez et al 2013 ;Wieloch et al 2012 ;Wu et al 2013 ), CAT (Ahamed et al 2006(Ahamed et al , 2008(Ahamed et al , 2011Wieloch et al 2012 ;Martinez et al 2013 ), and GPx (Diouf et al 2006 ;Jin et al 2006 ;Ahamed et al 2008 ) (Table 3 ).…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies examined Pb concentrations in immigrant women (Table 1) [41,42,43,44,45,46,47]. Mean Pb levels, where reported, ranged from geometric means (GM) of 0.78 μg/dL (95% CI: 0.57, 1.10) in immigrants to Canada [37] to 29.5 μg/dL (95% CI: 25.9, 33.1) in immigrant Pb-poisoned women exhibiting pica behaviour in New York City, USA [41].…”
Section: Scoping Review Resultsmentioning
confidence: 99%
“…Only one study [46] examined metal levels by stratifying based on years since arrival in country. Immigrant women to Taiwan ( n = 239), 67 coming from mainland China, with the rest originating from elsewhere in southeast Asia, were grouped into two categories: (1) recent immigrants (≤5 years since arrival); and (2) less recent immigrants (>5 years since arrival).…”
Section: Scoping Review Resultsmentioning
confidence: 99%